Analysis of the Related Influencing Factors of Hepatic Abscess Associated with Hepatobiliary Ischemic Necrosis after Cholangiocarcinoma Operation: Hepatic Abscess Associated with Hepatobiliary Ischemic Necrosis - Wang, Xianfeng; Lv, Qiaohong; Meng, Zhangge (Cellular and Molecular Biology, 2023)
To investigate related factors of liver abscess associated with hepatobiliary ischemic necrosis after cholangiocarcinoma surgery, 100 patients with cholangiocarcinoma requiring surgical resection were collected and divided into a test group (53 patients with liver abscess) and a control group (47 patients without liver abscess) according to presence or absence of liver abscess. Related factors were compared: gender, age, body mass index (BMI), body temperature at admission, duration of medical history, presence or absence of a history of diabetes, time of medical history, presence or absence of hepatolithiasis, absolute neutrophil count, absolute lymphocyte count (ALC), C-reactive protein, serum albumin (ALB), alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (AKP), direct bilirubin (DBIL), serum creatine, and presence or absence of anemia. Univariate analysis showed that BMI, age, gender, absolute lymphocyte count, serum ALB, AST, and time of medical history were significantly different between the two (P<0.05). Multivariate logistic regression analysis of the above influencing factors showed that independent influencing factors of postoperative liver abscess formation were: ALC<1.1*10^9/L (P<0.001, OR=23.459, 95% CI=8.529-64.576), AST≥40 U/L (P=0.012, OR=3.946, 95% CI=1.355-11.487), time of medical history≥21 days (P=0.010, OR=4.028, 95% CI=1.389-11.681). Decreased ALC, increased AST, and occurrence of acute biliary tract infection were independent factors for hepatobiliary ischemic necrosis-related liver abscess. Abnormal nutritional status, age, and gender were also the influencing factors of liver abscess.